Recruitment and Selection Practices on the Performance of Selected Public Sector Organisations in Nigeria - Okhaiti Anne Ugbodaga; Umar Abbas Ibrahim (Indonesian Scientific Publication, 2026)
Political patronage and bureaucratic rigidity have weakened merit-based hiring in Nigeria’s public sector. This study therefore investigated the effect of recruitment and selection practices on the performance of selected civil service-regulated public sector organisations in Nigeria, using a quantitative cross-sectional survey design. Data were collected from 378 valid respondents drawn from federal Ministries, Departments, and Agencies (MDAs) in Abuja via stratified random sampling and structured questionnaires. The findings revealed positive relationships between external recruitment practices and productivity, and between background/reference checks and productivity. The study’s novelty lies in its focus on the combined effect of these two recruitment and selection mechanisms within civil service-regulated organisations and its theoretical contribution to knowledge by extending Human Capital Theory to the underexplored context of Nigeria’s civil service, where regulatory frameworks, political patronage and lack of governance pre-employment verification are distinct constraints that shape talent acquisition outcomes. The practical implication of the study is that public sector organisations are to prioritise merit-based external recruitment practices and institutionalise comprehensive pre-employment background/reference checks into talent acquisition strategy for improved performance.